A stochastic smoothing method for nonsmooth global optimization - Norkin, V.I. (Кібернетика та комп’ютерні технології, 2020)
The paper presents the results of testing the stochastic smoothing method for global optimization of a multiextremal function in a convex feasible subset of the Euclidean space. Preliminarily, the objective function is extended outside the admissible region so that its global minimum does not change, and it becomes coercive.